Understanding chronic pain in the ubiquitous community: the role of open data - Monaco, Federico; Georgiadis, Emmanouil; Chatsiou, Kakia; Bonacaro, Antonio (Frontiers in Pain Research, 2023)
The combined use of social media, open data and artificial intelligence has the potential to support practitioners and empower patients/citizens living with persistent pain both as local and online communities. Given the availability of digital means, both practitioners and interested individuals can be connected in virtual communities and support each other from the comfort of their own places. Such digital means may represent new avenues for exploring the complexity of the pain experience.Patients' online interactions, data on effective treatments, and the ones collected by wearable devices may represent an incredible source of psychological, sociological, and physiological pain related information. Digital means might provide several solutions which enhance inclusiveness and motivate patients to share personal experiences limiting the sense of isolation in both rural and metropolitan areas. Capitalising on consensus of the usefulness of social media in enhancing the understanding of persistent pain and related subjective experiences via online communities and networks, we provide relevant scenarios where the effectiveness and efficiency of healthcare delivery might be improved by the adoption of the above-mentioned technologies. The aim of this perspective paper is to explore the potential of open data, social media, and artificial intelligence in improving persistent pain prevention and management via innovative non-biomedical approaches.